Utilising Virtual Reality in Car Visualisation - Tan, Teck Eng (2003)
This paper illustrates and investigates the potential of using 3D Studio Max in enhancing the car visualisation effects. 3D Studio Max is an alternative tool that can be used in presenting car visualisation. This paper describes the implementation processes and the lessons learned in the “findings” throughout the development process by using various software. The objectives are to obtain information on the process behaviour without a real implementation of the car physical body yet, shortening set up times of producing a car visualisation by utilising virtual reality (VR), minimising costs in terms of not creating the physical body of the car yet but through car visualisation to view on the car, and comparison of advantages and disadvantages between 3D Studio Max and Cortona VRML (Virtual Reality Modelling Language) Client-Overall the conclusions answer the objectives which have been stated in the early stage. First it allows obtaining information on the process behaviour without a real implementation of the car physical part. This is because from the preliminary design the specific kind of design is being set. Then through the design stage after the car visual&ion is being animated, the car visualisation can be seen without making the car model yet. Next the project answers the objective of shortening set up times because the project only takes 3 months to do the car visualisation. Besides it also minimise costs because we can see the final outcome through car visualisation. Lastly, the comparison advantages and disadvantages between 3D Studio Max and Cortona had been made. The significant from the project is that 3D Studio Max can serve as an alternative tool for car visualisation. However there are limitations of the software. If compared to Cortona, it is a better tool for interaction because the user can interact with the car visualisation by using the "walkthrough" option. Cortona also has its own limitations compare to 3D Studio Max. In future, the car visualisation can be implemented into designing the new industrial product features before implementing it.